Upaya Peningkatan Kreativitas Dan Percaya Diri Anak Melalui Lomba Keagamaan Di Sekolah Dasar - Nabilah Hendri Sasikirana1; Doris Rifqiyah Belgiz; Ria Putri Septiani; Mesra Surya Ariefin; Ardiansyah Ahsanul Hayat; Tri Winarsih; Achmad Farid Dedyansyah (CV. KAMPUS AKADEMIK PUBLISING, 2023)
The educational levels targeted for community service are elementary schools (SD) and junior high schools (SMP) in 3T areas (frontier, remote and disadvantaged). This community service uses a method of increasing children's creativity and self-confidence through religious competitions at SDN Purwokerto Ngimbang Elementary School. The positive impacts of this activity include providing additional insight and knowledge as well as skills in applying Islamic behavior in everyday life, as well as fostering student enthusiasm in take the courage to appear in public. This aims to ensure that students are more confident and able to explore their potential in supporting increased learning abilities.